The normal optic nerve head on heidelberg retina tomograph II. - Agarwal Harish (Indian Journal of Ophthalmology, 2003)
Purpose: To study the characteristics of the optic nerve head using a scanning laser ophthalmoscope, the Heidelberg Retina Tomograph II (HRT II), in a normal population and to determine the specificity of HRT II diagnostic indices in the study population. Methods: The optic nerve heads from 275 consecutive, randomly selected normal subjects were imaged on HRT II. Stereometric parameters were studied with respect to baseline variables such as age, gender, refractive error and disc size. The stereometric parameters and the results of Moorfields regression analysis (MRA) and discriminant function analysis were recorded. Results: The average disc size in the population under study was 2.34 + 0.47 mm[2]. Age and gender had no significant effect on stereometric parameters. Myopic discs were larger than hypermetropic discs. MRA had a specificity varying between 85.5% and 98.2% depending upon the criteria used to define an abnormal disc. The specificity of MRA decreased with increasing disc size. The RB (R Bathija) and FSM (F S Mikelberg) discriminant functions had specificities of 96.4% and 87.3% respectively. Conclusions: Estimation of stereometric parameters of a normal disc can be used to indicate an abnormal one. Moorfields regression analysis and discriminant functions have a high specificity in our normal population; however, caution must be exercised in interpreting the results for a disc area larger than 3 mm 2.